2015
DOI: 10.1128/aac.01347-15
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Piperacillin in the Early Phase of Septic Shock: Does Standard Dosing Result in Therapeutic Plasma Concentrations?

Abstract: e Antibiotic dosing in septic shock patients poses a challenge for clinicians due to the pharmacokinetic (PK) variability seen in this patient population. Piperacillin-tazobactam is often used for empirical treatment, and initial appropriate dosing is crucial for reducing mortality. Accordingly, we determined the pharmacokinetic profile of piperacillin (4 g) every 8 h, during the third consecutive dosing interval, in 15 patients treated empirically for septic shock. We developed a population pharmacokinetic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
1
28
1
Order By: Relevance
“…A flowchart of study selection for each drug is provided in Figure . A total of 2082 articles were identified and screened, with 130 studies included in the final analysis . Some studies provided PK parameters for two drugs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of study selection for each drug is provided in Figure . A total of 2082 articles were identified and screened, with 130 studies included in the final analysis . Some studies provided PK parameters for two drugs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, clearance of piperacillin is highly dependent on the renal function of the study cohort, and this in many ways explains the different reported mean piperacillin clearances in different patient populations. In the critically ill, for instance, clearance could be elevated (e.g., 17.1 liters [18]) or similar/slightly higher (e.g., 13.8 liters/h [15,16] and 14.0 Ϯ 7.1 liters [17]) or may even be reduced (e.g., 3.6 liters/h [19] and 5.6 Ϯ 3.2 liters/h [12]) compared to healthy volunteers (13). It could be particularly high in those patients with burns and trauma (20).…”
Section: Discussionmentioning
confidence: 99%
“…Serial blood samples were collected over one dosing interval for up to three consecutive days if piperacillin-tazobactam treatment was maintained. The sampling times were optimized in the PopED (version 2.13) optimal design tool (42), given a prior piperacillin PK model for septic shock patients (4), and were focused on providing information on the population PK and the individual fT MIC (for further details, see A. N. Kristoffersson's unpublished presentation at the Population Optimum Design of Experiments [PODE] workshop, Uppsala, Sweden, 20 June 2016 [http:// www.maths.qmul.ac.uk/~bb/PODE/PODE2016_AKristoffersson.pdf ]). At the first day after study inclusion, each patient had three blood samples drawn.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that standard treatment with piperacillin-tazobactam (4 g/0.5 g) every 8 h (q8h) may result in subtherapeutic concentrations in septic shock patients admitted to an intensive care unit (ICU) (4). In the present study, we wanted to assess if there is a similar risk of subtherapeutic concentrations among less critically ill septic patients admitted to a general ward.…”
mentioning
confidence: 96%
See 1 more Smart Citation